1999
DOI: 10.1074/jbc.274.42.30001
|View full text |Cite
|
Sign up to set email alerts
|

Unique Lipoproteins Secreted by Primary Astrocytes From Wild Type, apoE (−/−), and Human apoE Transgenic Mice

Abstract: Composition of central nervous system lipoproteins affects the metabolism of lipoprotein constituents within the brain. The ⑀4 allele of apolipoprotein E (apoE) is a risk factor for Alzheimer's disease via an unknown mechanism(s). As glia are the primary central nervous system cell type that synthesize apoE, we characterized lipoproteins secreted by astrocytes from wild type (WT), apoE (؊/؊), and apoE transgenic mice expressing human apoE3 or apoE4 in a mouse apoE (؊/؊) background. Nondenaturing size exclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
163
2
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 193 publications
(181 citation statements)
references
References 70 publications
15
163
2
1
Order By: Relevance
“…Purification and size analysis of apoE-containing lipoproteins secreted by immortalized astrocytes Primary astrocytes secrete nascent murine and human apoE into apoE-containing HDLs that are disc-like in appearance since they contain cholesterol and phospholipid but no cholesteryl-ester core (DeMattos et al, 2001b;Fagan et al, 1999;LaDu et al, 1998). To determine if the apoE2-, apoE3-, and apoE4-secreting Table 1 Quantitation of the level of apoE present in serum-free conditional media from immortalized astrocytes derived from APOE2, APOE3, and APOE4 knock-in mice Cells were grown in 6-well plates.…”
Section: Isolation and Characterization Of Immortalized Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purification and size analysis of apoE-containing lipoproteins secreted by immortalized astrocytes Primary astrocytes secrete nascent murine and human apoE into apoE-containing HDLs that are disc-like in appearance since they contain cholesterol and phospholipid but no cholesteryl-ester core (DeMattos et al, 2001b;Fagan et al, 1999;LaDu et al, 1998). To determine if the apoE2-, apoE3-, and apoE4-secreting Table 1 Quantitation of the level of apoE present in serum-free conditional media from immortalized astrocytes derived from APOE2, APOE3, and APOE4 knock-in mice Cells were grown in 6-well plates.…”
Section: Isolation and Characterization Of Immortalized Cellsmentioning
confidence: 99%
“…Glia (astrocytes and microglia) are cells in the CNS that produce the majority of apoE (Boyles et al, 1985;LaDu et al, 1998;Nakai et al, 1996;Pitas et al, 1987a;Stone et al, 1997), with astrocytes appearing to produce the preponderance of this protein. It has been demonstrated that astrocytes secrete apoE in nascent HDL-like lipoprotein particles, which contain cholesterol and phospholipid but lack a cholesteryl-ester core (DeMattos et al, 2001b;Fagan et al, 1999;LaDu et al, 1998). Since the physiological activity of apolipoproteins and their interactions with other molecules (e.g., Ah and receptors) can be markedly influenced by the size, composition, and type of lipoprotein particle with which they are associated, it is important to study the properties and interactions of apoE derived from the CNS or CNS cells.…”
Section: Introductionmentioning
confidence: 99%
“…We focused on ApoE as a candidate gene for three reasons: (1) ApoE is located on chromosome 19q thought to contain susceptibility genes associated with febrile seizures, (2) three different genotypes (ApoE2, ApoE3, ApoE4), linked to single nucleotide polymorphisms, have been identified in humans, and (3) apolipoprotein E found in the brain is synthesized in astrocytes and plays a major role in the maintenance of lipid homeostasis and vesicular trafficking [20,21]. In Europeans free of any neurological disorders, the distribution of different alleles is stable, with an ApoE2 frequency of 0.068, an ApoE3 frequency of 0.813 and an ApoE4 frequency of 0.119 [22].…”
Section: Introductionmentioning
confidence: 99%
“…A doublet can be observed at about 36kDa, in addition to a second band at about 80kDa (arrowheads). It has been suggested that doublets may reflect apoE sialylation, 8,31 whereas the band at about 80kDa represents an apoE complex not dissociated by SDS. 31,32 No qualitative differences in staining were observed among the 3 genotypes.…”
Section: Figmentioning
confidence: 99%
“…Doublets at 36kDa have been described previously and are thought to result from apoE sialylation. 8,31 In addition, apoE complexes that are not dissociated by SDS have been reported at a molecular weight of about 80kDa. 31,32 APOE genotyping: polymerase chain reaction-restriction fragment length polymorphism…”
Section: Apoe Western Blotmentioning
confidence: 99%